TOLL ROAD TARIFF AND TOLL COLLECTION INTEGRATION POLICY IN INDONESIA: ADVANCING TOWARDS AN EFFICIENT, FAIR, AND SUSTAINABLE SYSTEM - Muljono , Slamet; Daramita , Ratu Intan Febry (Jurnal HPJI (Himpunan Pengembangan Jalan Indonesia), 2025)
Abstract Toll tariff integration in Indonesia represents a significant reform in transportation policy, aimed at enhancing efficiency, equity and sustainability. This paper explores the integration process from policy, technical, to institutional perspectives, using case studies from Greater Jakarta, Greater Surabaya, and Greater Medan regions. Findings show that integration improves average travel speed (up to 9% in Greater Jakarta region), reduces toll gate congestion, and enhances logistics cost efficiency. Nevertheless, key challenges persist, including infrastructure readiness, equitable revenue sharing among operators, and public acceptance. This study recommends a phased implementation strategy, tariff simulations based on users’ Ability to Pay and Willingness to Pay, and strengthened inter-stakeholder coordination to ensure the success of toll road inte-gration policies. Keywords: tariff integration; transportation efficiency; sustainability; Willingness to Pay; Ability to Pay Abstrak Integrasi tarif tol di Indonesia merupakan reformasi yang signifikan dalam kebijakan transportasi, yang bertujuan untuk meningkatkan efisiensi, kesetaraan, dan keberlanjutan. Makalah ini mengeksplorasi proses integrasi mulai dari perspektif kebijakan, teknis, hingga kelembagaan, menggunakan studi kasus di wilayah-wilayah Jabodetabek, Surabaya Raya, dan Medan Raya. Temuan yang diperoleh menunjukkan bahwa integrasi meningkatkan kecepatan perjalanan rata-rata (hingga 9% di Jabodetabek), mengurangi kemacetan di gerbang tol, dan meningkatkan efisiensi biaya logistik. Namun demikian, tantangan utama tetap ada, termasuk kesiapan infrastruktur, pembagian pendapatan yang adil di antara para operator, dan penerimaan publik. Studi ini merekomendasikan strategi implementasi bertahap, simulasi tarif berdasarkan Kemampuan untuk Membayar dan Kesediaan untuk Membayar pengguna, dan penguatan koordinasi antarpemangku kepentingan untuk memastikan keberhasilan kebijakan integrasi jalan tol. Kata-kata kunci: integrasi tarif; efisiensi transportasi; keberlanjutan; Kesediaan untuk Membayar; Kemam-puan untuk Membayar